Carbon‐Nanotube‐Appended PAMAM Dendrimers Bearing Iron(II) α‐Keto Acid Complexes: Catalytic Non‐Heme Oxygenase Models1. Issue 39 (14th June 2019) - Sheet, Debobrata; Bera, Abhijit; Fu, Yang; Desmecht, Antonin; Riant, Olivier; Hermans, Sophie
Abstract: Poly(amidoamine) dendrimers grafted on carbon nanotubes have been appended with iron(II)‐α‐keto acid (benzoylformate) complex of polypyridyl ligand to design artificial non‐heme oxygenase model. This nano‐enzyme was applied for selective catalytic oxidation of organic molecules. Although the carbon nanotubes serve as a robust heterogeneous platform, the amine terminals of dendrimers provide catalysts binding sites and the amide bonds provide a necessary second coordination sphere similar to the enzymatic polypeptide chains. Such a hybrid design prevented the deactivation of the primary active sites leading to 8 times faster oxidative decarboxylation rates than those of its homogeneous analogue. An electrophilic iron(IV)‐oxo intermediate has been intercepted, which catalyzes the selective oxidation of alcohols to aldehydes and incorporates single oxygen atoms into sulfides and olefins by using aerial oxygen with multiple turnover numbers. The catalyst was consecutively regenerated three times by mild chemical treatment and showed negligible loss of activity. Abstract : Artificial oxygenases designed through decoration of carbon nanotubes with PAMAM dendrimers attached to iron(II)‐benzoylformate active sites displayed dramatically enhanced reaction rates compared to homogeneous analogues. An iron(IV)‐oxo oxidant was intercepted to catalyze the selective aerobic oxidation of alcohols, olefins, and sulfides thereby representing the best heterogeneous catalytic functional model of α‐KG dependent enzymes.